Returning negative results from large‐scale genomic screening: Experiences from the eMERGE III network. Issue 2 (8th December 2020) - Finn, Kelsey Stuttgen; Lynch, John; Aufox, Sharon; Bland, Sarah; Chung, Wendy; Halverson, Colin; Hebbring, Scott; Hoell, Christin; Holm, Ingrid; Jarvik, Gail; Kullo, Iftikhar; Leppig, Kathleen; et al.
Abstract: Population‐based genomic screening has the potential to improve health outcomes by identifying genetic causes of disease before they occur. While much attention has been paid to supporting the needs of the small percentage of patients who will receive a life‐altering positive genomic screening result that requires medical attention, little attention has been given to the communication of negative screening results. As there are currently no best practices for returning negative genomic screening results, we drew on experiences across the electronic medical records and genomics (eMERGE) III Network to highlight the diversity of reporting methods employed, challenges encountered in reporting negative test results, and "lessons learned" across institutions. A 60‐item survey that consisted of both multiple choice and open‐ended questions was created to gather data across institutions. Even though institutions independently developed procedures for reporting negative results, and had very different study populations, we identified several similarities of approach, including but not limited to: returning results by mail, placing results in the electronic health record via an automated process, reporting results to participants' primary care provider, and providing genetic counseling to interested patients at no cost. Differences in procedures for reporting negative results included: differences in terminology used to describe negative results, definitions of negative results, guidance regarding the meaning of negative results for participants and their family members, and recommendations for clinical follow up. Our findings highlight emerging practices for reporting negative genomic screening results and highlight the need to create patient education and clinical support tools for reporting negative screening results.